Clinical Management of Two Root Resorption Cases in Endodontic Practice - Jozef Mincik; Daniel Urban; Silvia Timkova (Case Reports in Dentistry)
Root resorption is a pathological process involving loss of hard dental tissues. It may occur as a consequence of dental trauma, orthodontic treatment, and bleaching, and occasionally it accompanies periodontal disease. Although the mechanism of resorption process is examined in detail, its etiology is not fully understood. Wide open apical foramen is more difficult to manage and the root canal may often overfill. In this report we present two cases of root resorption and describe means for its clinical management. We conclude that useful measure of a success or failure in managing root resorption is the persistence of the resorption process. It is a clear sign of an active ongoing inflammatory process and shows the clinical need for retreatment.